Impact of hybrid power generation on voltage, losses, and electricity cost in distribution networks - Ates, Yavuz; Gokcek, Tayfur; Arabul, Ahmet Yigit (Tubitak Scientific & Technological Research Council Turkey, 2021)
Energy and its capacity has emerged as one of the biggest distribution challenges all over the world. The existing grid becomes insufficient along with the expansion of the consumption. Therefore, the number of distributed generation (DG) in distribution networks increases and it allows us to sell back the extra energy. However, the efficiency of energy must be maintained into optimal values from the grid to the end-users. In spite of a lot of advantages of DG units, there are some disadvantages like fluctuations in voltage, increments of power losses, wrong protection coordination, harmonic and energy quality issues etc.. If the location, capacity, control mode, and type of DG resources cannot be designed optimally or the environment impacts such as wind speed and irradiation level cannot be considered before the integration in distribution networks, the integration results may lead to especially inefficiency of energy in terms of the voltage profile and the power losses. It is aimed to reduce the daily cost of an industrial area as well as improving the voltage profile and reducing the power losses by integrating DG units considering convenient location and dynamic price values. In this study, the impact of hybrid distributed power resources on voltage improvement, power losses, and electricity cost of the IEEE 13-bus test system are examined using Electrical Transient Analyzer Program software. In the simulation, the photovoltaic system and type 3 wind turbine generator are designed as 500 kW and integrated at bus 671 and bus 675 with four cases. Finally, the results obtained for voltage profiles and power losses of the entire system and total electricity cost of the industrial area are presented as comparative charts.
Keywords: Hybrid distributed generation; wind energy; photovoltaic energy; voltage profile; power losses; electricity cost; DISTRIBUTION-SYSTEMS; IMPLEMENTATION; MANAGEMENT; BATTERY; Computer Science; Engineering